Contribution of body segments to aerodynamic forces during takeoff in ski jumping - Yamamoto, K.; Takeda, T.; Tsubokura, M.; Baleriola, S.; Onishi, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In the series of movement involved in the ski jumping technique, the takeoff motion is considered to be the most important phase to determine the performance (Schwameder, 2008, Virmavirta et al., 2009). Since ski jumpers are required to change their posture from the crouching posture to the flight posture within an extremely short period of time, the aerodynamic force acted upon a ski jumper changes dynamically (Yamamoto et al., 2015). The aim of this study was to investigate the contribution of each body segment to the aerodynamic force during the motion. Methods Three dimensional surface model of a ski jumper was obtained by 3-D laser scanning of an active ski jumper, and divided the model into 15 body segments with joint mobility. Two sets of motion data were generated using the video analysis of ski jumper`s takeoff motion (world-class jumper A and less-experienced junior jumper B). The CFD method adopted for this study was based on Large-Eddy Simulation. The incoming velocity was set to 23.23 m/s. The aerodynamic force, pressure distribution on the model`s surface and contribution of each body segment to the aerodynamic force were calculated and then were compared between the two jumpers. Results Regarding the lift force, although jumper A`s lift force was less in the in-run posture, it became greater than that of jumper B at the end of the movement. Lift forces acted upon Jumper A and B at the posture right before the takeoff were 62.1N and 57.6N, respectively. The body segment which was the most contributive for the lift force was a trunk (A: 63.8%, B: 56.8%). The second contributive segments were the arms (A: 31.5%, B: 32.5%). The drag force acting upon jumper A was weaker than that acting upon jumper B through the whole movement. Those were 60.7N for A and 94.7N for B at the posture right before the takeoff. However, the trunk segment had a great influence to drag as well as lift (A: 40.1%, B: 60.1%), and the contribution of the arms was relatively low (A: 4.0%, B: 9.4%). Discussion As for the lift, the total contribution of the trunk and the arms segments reached approximately 90%, and it was suggested that trunk movement was important aerodynamically. The contribution of the trunk segment to drag was also high, but the relatively low contribution of the arms segments was an interesting finding. These results suggested that the movements of the arms would have an influence in increasing lift and restraining drag.